The philosophy of psychology - Botterill, George; Carruthers, Peter, 1952- (Cambridge ; New York : Cambridge University Press, 1999)
This book presents an original and accessible analysis of the relationship between common-sense, or 'folk', psychology and contemporary scientific psychology, focussing on the ways in which cognitive science presents a challenge to our common-sense self image. It is designed as a textbook for upper-level undergraduate and beginning postgraduate students in philosophy and cognitive science. As a text that not only surveys but advances the debates on the topics discussed, it will also be of interest to researchers working in these areas.
Introduction: some background -- Folk-psychological commitments -- Modularity and nativism -- Mind-reading -- Reasoning and irrationality -- Content for psychology -- Content naturalised -- Forms of representation -- Consciousness: the final frontier?
Includes bibliographical references (pages 272-289) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Psychology -- Philosophy; Cognition; Philosophy; Psychological Theory; Cognition; Cognitive Science; Philosophy; Psychologie -- Philosophie; Cognition; Philosophie; cognition; philosophy; PSYCHOLOGY -- General; Philosophy; Cognition; Psychology -- Philosophy; Psychologie; Philosophie; Psychologie; Filosofische aspecten; Psychologie et philosophie; Cognition; Psychology; Philosophy; Electronic books; Electronic books